2009
DOI: 10.1007/s00415-009-5334-9
|View full text |Cite
|
Sign up to set email alerts
|

The thalamic ultrastructural abnormalities in paroxysmal kinesigenic choreoathetosis: a diffusion tensor imaging study

Abstract: Paroxysmal kinesigenic choreoathetosis (PKC) is a rare neurologic disorder. There are not apparent morphological changes in patients with idiopathic PKC. The purpose of this study is to determine whether ultrastructural changes are in the brain of patients with idiopathic PKC using diffusion tensor imaging. From May 2007 to August 2008, seven patients with idiopathic PKC were included. The mean age at initial onset was 11.7 +/- 3.1 (range 8-17) years, and the mean disease duration was 6.9 +/- 5.1 (range 1-14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…This provided us with further understanding of the pathophysiological mechanisms of PKD. In comparison with this, several other neuroimaging studies suggested abnormalities in other portions of the basal ganglia-thalamo-cortical circuitry in PKD, involving caudate nuclei [9], globus pallidus [12], thalamus [11,16,17]. This difference may be due to different imaging modalities, different state and relatively small sample sizes, indicating the underlying mechanisms may be rather complicated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This provided us with further understanding of the pathophysiological mechanisms of PKD. In comparison with this, several other neuroimaging studies suggested abnormalities in other portions of the basal ganglia-thalamo-cortical circuitry in PKD, involving caudate nuclei [9], globus pallidus [12], thalamus [11,16,17]. This difference may be due to different imaging modalities, different state and relatively small sample sizes, indicating the underlying mechanisms may be rather complicated.…”
Section: Discussionmentioning
confidence: 81%
“…Recent functional neuroimaging studies revealed increased amplitude of low frequency fluctuation (ALFF) in bilateral putamen and other cortical areas in the cortical-basal ganglia circuitry [14,15], which implies excessive spontaneous neural activity during resting state. Moreover, microstructural and macrostructural abnormalities have been detected in the thalamus [16,17]. These previous studies suggested regional abnormalities in the basal gangliathalamo-cortical circuitry in PKD, yet are limited to regional alterations, unable to manifest the functional connectivity related to this circuitry.…”
Section: Introductionmentioning
confidence: 93%
“…Analysis of functional neuroimaging in patients with PKD has failed to define the distinct neural characteristics of PKD-D and PKD-C. 9,10,13,15,17,31 Consequently, diagnosis remains based on clinical symptoms that are diverse and vary between individuals. 5 To this end, we investigated the distinct neural characteristics of PKD-D and PKD-C.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Earlier structural 12,15 and functional 10,17 studies suggested bilateral abnormality in cortical-basal ganglia-thalamus circuitry regions, including thalamus and putamen, a common pathophysiology in PKD. From the relatively detailed clinical information, we concluded that attacks were predominantly left-sided in 12 patients, including unilateral, bilateral, and alternating cases, and right-sided in 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Paroxysmal kinesigenic dyskinesia (PKD) is a rare movement disorder, characterized by disruption of both structural and functional properties in the thalamus and basal ganglia. These subcortical structures underlie the pathophysiology of PKD . PKD symptoms involve brief episodes of abnormal movement that are triggered by sudden voluntary movements.…”
mentioning
confidence: 99%